Faking liberties religious freedom in American-occupied Japan - Thomas, Jolyon Baraka 1978- (Chicago London The University of Chicago Press, 2019)
Intro -- CONTENTS -- PROLOGUE -- CONVENTIONS -- INTRODUCTION -- A PREOCCUPATION WITH RELIGIOUS FREEDOM -- 1. THE MEIJI CONSTITUTIONAL REGIME AS A SECULARIST SYSTEM -- 2. WHO NEEDS RELIGIOUS FREEDOM? -- 3. DOMESTIC PROBLEMS, DIPLOMATIC SOLUTIONS -- 4. IN THE ABSENCE OF RELIGIOUS FREEDOM -- THE OCCUPATIONOF RELIGIOUS STUDIES -- 5. STATE SHINTO - AS AHERETICAL SECULARISM -- 6. WHO WANTS RELIGIOUS FREEDOM? -- 7. UNIVERSAL RIGHTS, UNIQUE CIRCUMSTANCES -- 8. OUT OF THE SPIRITUAL VACUUM -- CONCLUSION -- EPILOGUE -- ACKNOWLEDGMENTS -- NOTES -- REFERENCES -- INDEX.
Keywords: Japan-History-Allied occupation, 1945-1952; Freedom of religion-Japan-History-20th century; Electronic books